Mitochondrial DNA Stress Primes the Antiviral Innate Immune Response - West, A. Phillip (Nature, 2015)
Mitochondrial DNA (mtDNA) is normally present at thousands of copies per cell and is packaged into several hundred higher-order structures termed nucleoids(1). The abundant mtDNA-binding protein, transcription factor A mitochondrial (TFAM), regulates nucleoid architecture, abundance, and segregation(2). Complete mtDNA depletion profoundly impairs oxidative phosphorylation (OXPHOS), triggering calcium-dependent stress signaling and adaptive metabolic responses(3). However, the cellular responses to mtDNA instability, a physiologically relevant stress observed in many human diseases and aging, remain ill-defined(4). Here we show that moderate mtDNA stress elicited by TFAM deficiency engages cytosolic antiviral signaling to enhance the expression of a subset of interferon-stimulated genes (ISG). Mechanistically, we have found that aberrant mtDNA packaging promotes escape of mtDNA into the cytosol, where it engages the DNA sensor cGAS and promotes STING-IRF3-dependent signaling to elevate ISG expression, potentiate type I interferon responses, and confer broad viral resistance. Furthermore, we demonstrate that herpesviruses induce mtDNA stress, which potentiates antiviral signaling and type I interferon responses during infection. Our results further demonstrate that mitochondria are central participants in innate immunity, identify mtDNA stress as a cell-intrinsic trigger of antiviral signaling, and suggest that cellular monitoring of mtDNA homeostasis cooperates with canonical virus sensing mechanisms to fully license antiviral innate immunity.